2016
DOI: 10.1016/j.molp.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

SERK Family Receptor-like Kinases Function as Co-receptors with PXY for Plant Vascular Development

Abstract: In Arabidopsis, the CLAVATA3/EMBRYO SURROUNDING REGION-RELATED (CLE) peptides play important roles in regulating proliferation and differentiation of plant-specific stem cells. Although receptors of CLEs are reported to be leucine-rich repeat receptor kinases, the mechanisms underlying CLE-induced receptor activation remain largely unknown. Here we show that SOMATIC EMBRYOGENESIS RECEPTOR KINASEs (SERKs) serve as co-receptors in CLE41/TDIF-PXY signaling to regulate plant vascular development. TDIF induces inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 36 publications
3
102
1
6
Order By: Relevance
“…However, in contrast to HAESA, the isolated PXY ectodomain binds CLE41/44 with nanomolar (10–30 nM), not micromolar, affinity (Fig EV1B) . Interestingly, the SERK1 ectodomain binds relatively weakly to CLE41/44‐bound PXY, suggesting that, despite their structural similarities, the activation mechanisms for HAESA and PXY may differ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to HAESA, the isolated PXY ectodomain binds CLE41/44 with nanomolar (10–30 nM), not micromolar, affinity (Fig EV1B) . Interestingly, the SERK1 ectodomain binds relatively weakly to CLE41/44‐bound PXY, suggesting that, despite their structural similarities, the activation mechanisms for HAESA and PXY may differ .…”
Section: Discussionmentioning
confidence: 99%
“… A, BStructural superposition of HAESA‐IDA‐SERK1 (PDB‐ID 5IYX, HAESA in light blue, IDA in dark blue, and SERK1 in cyan) (Santiago et al ) with a PXY‐CLE41/44‐SERK2 complex (PDB‐ID 5GQR, PXY in gold, IDA in yellow, and SERK2 in orange) (Zhang et al ). The complexes closely align with an r.m.s.d.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of flg22 does not lead to a conformational change in the FLS2. The PEPR1-Pep1, HAESA-IDA-SERK1, PXY-TDIF-SERK2, and RGFR1-RGF1-BAK1 complexes also adopt a conformation strikingly similar to the FLS2-flg22-BAK1 complex (Figure 1; Tang et al, 2015;Santiago et al, 2016;Song et al, 2016;Zhang et al, 2016). The PSKR1-PSK-SERK1 structure showed a different mechanism for ligand binding and receptor complex formation.…”
Section: Ligand Binding and Oligomerization Of Prr Receptor Complexesmentioning
confidence: 99%
“…Molecular and genetic studies showed that SERKs are also recruited to EFR, PEPRs, and Xa21 upon ligand binding and required for signaling (Roux et al, 2011;Chen et al, 2014;Yamada et al, 2016a). In addition, LRR-RKs for peptide hormones, including tracheary element differentiation inhibitory factor (TDIF), INFLORESCENCE DEFIECIENT IN ABSCISSION (IDA), PHYTOSULFOKINE (PSK), and ROOT GROWTH FACTORS (RGFs), also require SERKs for function Tang et al, 2015;Song et al, 2016;Santiago et al, 2016;Zhang et al, 2016). The FLS2-flg22-BAK1 complex showed that flg22 adopts a linear conformation and binds to FLS2 LRR3-16 in the same N-terminal to C-terminal orientation (Figure 1; Sun et al, 2013).…”
Section: Ligand Binding and Oligomerization Of Prr Receptor Complexesmentioning
confidence: 99%
“…The LRR-RKs CLAVATA 1 (CLV1), BARELY ANY MERISTEM 1-3 (BAM1-3), RECEPTOR-LIKE PROTEIN KINASE 2 (RPK2), and TRACHEARY ELEMENT DIFFERENTIATION FACTOR RECEPTOR/PHLOEM INTERCALATED WITH XYLEM (TDR/PXY) sense small, posttranslationally modified CLV3/EMBRYO SURROUNDING REGION (ESR)-RELATED (CLE) peptide hormones, including CLV3, to maintain plant stem cell populations in the shoot and in the root (24,30,32,33,45,88,89,106,114,145). A family of secreted peptide hormones with structural similarities to CLEs, the INFLORESCENCE DEFICIENT IN ABSCISSION-LIKE (IDL) peptides, trigger abscission and cell separation processes in plants by binding to the LRR-RKs HAESA and HAESA-LIKE 2 (HSL2) (15,67,100,126).…”
Section: Architecture Of Plant Receptor Kinases (Rks) Receptor-like mentioning
confidence: 99%